Outcome of Graves' Disease Patients Treated with Radioactive Iodine Therapy at RSCM: Preliminary Study - Nur Rusyda Kuddah; Imam Subekti; Alvita Dewi Siswoyo (PP PERKENI, 2025)
Graves’ disease (GD) constitutes 60-80% of all cases of thyrotoxicosis worldwide, typically managed with anti-thyroid drugs (ATD) as first-line therapy. If a patient failed to achieve remission after 18 months or had an ATD allergy, can continue to choose radioactive iodine (RAI131) as definitive therapy. Research on the use of RAI in GD remains limited in Indonesia, and nuclear medicine facilities are not yet widely distributed. To assess the treatment outcome of fixed-dose RAI131 10 mCi and the contributing factors involved.Methods: This was a retrospective observational study involving 10 GD patients who underwent RAI at RSCM. Secondary data were collected consecutively from medical records. The outcome study was the prevalence of hypothyroidism in the 3rd and/or 6th month following RAI. Serum free T4 and TSHs levels were evaluated at baseline, and at 3, 6, and 12 months post-RAI. Inclusion criteria consisted of GD patients who failed to achieve remission with ATD and subsequently underwent RAI at the Department of Nuclear Medicine, RSCM. At 3 months post-RAI131, 40% of subjects achieved hypothyroidism, 40% had subclinical hyperthyroidism, and 20% reached euthyroid status. At 6 months, 80% of subjects remained with subclinical hyperthyroidism, 10% experienced worsening hyperthyroidism and 10% had developed permanent hypothyroidism. No worsening of Graves’ ophthalmopathy (GO) was observed during the study period. RAI is a safe and effective definitive treatment for GD. Nevertheless, good interdisciplinary collaboration is essential to ensure the successful hypothyroidism achievement as primary therapeutic goals.